Are extracellular vesicles new hope in clinical drug delivery for neurological disorders?. (March 2021) - Muhammad, S.A.
Abstract: Cells secrete extracellular vesicles (EVs) for intercellular communication. EVs are natural nanovesicles that are surrounded by lipid bilayer for delivery of assorted cargoes for therapeutic purposes. In addition to their therapeutic roles, these vesicles are potential drug delivery systems. Exosomes are the most studied EVs as the delivery carriers that can cross the blood-brain barrier (BBB) because of their nanosize. BBB is a diffusion barrier that is selective for small molecules to transit from blood to the brain. This barrier has been an obstacle for the delivery of drugs to the brain for the treatment of neurological disorders (NDs). For efficient drug delivery, synthetic vesicles such as liposomes have been employed as carriers for delivery of therapeutic molecules in clinical practice. However, these delivery systems are not without drawbacks. Among the limitations of these drug carriers include recognition by the body as foreign particles that encounter multiple defence systems that could recognize, neutralize and eliminate them. EVs are natural vesicles that may circumvent the body defence system to remain in systemic circulation for a long time. This unique property made them excellent drug delivery vehicles for clinical application. Here I discuss the progress, challenges and future directions of EVs (especially exosomes) as vehicles for targeted delivery of drug and at the same time deliver their cargoes for regenerative purposes in NDs. Recent developments in bioengineering and microfluidic technologies, which hold promise for clinical-grade production of EVs as drug delivery systems for NDs are also highlighted. Graphical abstract: Image 1 Highlights: Extracellular vesicles (EVs) are vesicles that are released by the cells for intercellular communication. EVs, particularly exosomes are potential therapeutic molecules and drug delivery systems. Exosomes can deliver their bioactive cargoes and drugs across the blood-brain barrier for NDs. . Exosomes can increase the bioavailability & decrease the toxicity of the loaded drugs for tissue repair & neuro-regeneration.